2017
DOI: 10.3390/ijms19010071
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Identification and Characterization of Potato Circular RNAs in Response to Pectobacterium carotovorum Subspecies brasiliense Infection

Abstract: Little information about the roles of circular RNAs (circRNAs) during potato-Pectobacterium carotovorum subsp. brasiliense (Pcb) interaction is currently available. In this study, we conducted the systematic identification of circRNAs from time series samples of potato cultivars Valor (susceptible) and BP1 (disease tolerant) infected by Pcb. A total of 2098 circRNAs were detected and about half (931, 44.38%) were intergenic circRNAs. And differential expression analysis detected 429 significantly regulated cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 51 publications
3
41
0
Order By: Relevance
“…Recently, although the involvement of circRNAs in plant tolerance to abiotic stress has been reported in several species [19][20][21]26], their role has rarely been reported in soybean [30], especially under LP stress. In the present study, to identify and explore how circRNAs respond to LP stress in soybean, root samples of two representative soybean genotypes, NN94156 and Bogao, which present significant differences in their traits related to P-use efficiency, were used to construct RNA-seq libraries under LP (5 μM, -P) and HP (500 μM, +P, control) conditions.…”
Section: Identification and Characteristics Of Circrnas Responsive Tomentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, although the involvement of circRNAs in plant tolerance to abiotic stress has been reported in several species [19][20][21]26], their role has rarely been reported in soybean [30], especially under LP stress. In the present study, to identify and explore how circRNAs respond to LP stress in soybean, root samples of two representative soybean genotypes, NN94156 and Bogao, which present significant differences in their traits related to P-use efficiency, were used to construct RNA-seq libraries under LP (5 μM, -P) and HP (500 μM, +P, control) conditions.…”
Section: Identification and Characteristics Of Circrnas Responsive Tomentioning
confidence: 99%
“…Unlike traditional linear RNAs, circRNAs are generated from head-to-tail back-splicing; thus, they do not have the terminal 5 0 cap and the 3 0 polyadenylated tail structures found in linear genes [18]. Increasing amounts of evidence have indicated that circRNAs are commonly produced by thousands of genes and have substantial functions in regulating gene expression at multiple levels in eukaryotic cells [19]. For example, circRNAs can function as transcriptional and posttranscriptional regulators, miRNA sponges, small nucleolar RNAs (snoRNAs), RNA processing intermediates, and transcriptional cis-regulators [19][20][21].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Plant circRNAs have been found to function during fiber development, flowering, and fruit coloration based on spatial-and/or tissue-specific expression patterns (Tan et al, 2017;Wang et al, 2017c;Tong et al, 2018). The expression of plant circRNAs also responds to abiotic and biotic stimuli, including pathogen invasion (Zuo et al, 2016;Wang et al, 2017c;Zhou et al, 2017;Ghorbani et al, 2018;Xiang et al, 2018;Gao et al, 2019). For example, the accumulation of a set of circR-NAs is altered in kiwifruit upon canker pathogen infection (Wang et al, 2017c).…”
mentioning
confidence: 99%